2006
DOI: 10.1097/01.ccm.0000242158.28619.09
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal lymph flow in an endotoxin sepsis model: Influence of spontaneous breathing and mechanical ventilation*

Abstract: Endotoxin increases lymph flow from the abdomen. Mechanical ventilation with high PEEP impedes lymph drainage and could increase lymph production. Spontaneous breathing increases flow and improves drainage of abdominal edema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…Both positive pressure ventilation and intrathoracic insufflation increase the intrathoracic pressure and should have negatively affected the MB flow through the TD. Lattuada and Hedenstiema (2006) also concluded that spontaneous breathing increases lymph flow in pigs in comparison to mechanically-ventilated pigs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both positive pressure ventilation and intrathoracic insufflation increase the intrathoracic pressure and should have negatively affected the MB flow through the TD. Lattuada and Hedenstiema (2006) also concluded that spontaneous breathing increases lymph flow in pigs in comparison to mechanically-ventilated pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Also, we hypothesised that the previous injection of iohexol into the left popliteal lymph node should not have further influenced the lymphatic flow, because the interval between the two injections was more than 30 min. As lymphatic flow in pigs has been estimated to be between 2.5 and 6.9 ml/min (Lattuada and Hedenstiema 2006) iohexol should have disappeared from the lymph vessels at the time of MB injection.…”
Section: Discussionmentioning
confidence: 99%
“…TD drainage was previously described as research tool used in mice and rats [3], rabbits [4], dogs [5], sheep [6], and pigs [7]. Such intervention can be surgically demanding, especially in small-animal models [3,8].…”
Section: Introductionmentioning
confidence: 99%
“…Lattuada et al [57] found that endotoxin increased thoracic lymph flow in anesthetised pigs, whereas IAH decreased lymph flow irrespective of whether the pigs were septic or not.…”
Section: Abdominal Lymph Flow In Critically Ill Patients With Iahmentioning
confidence: 99%
“…Therefore, in critically ill patients with abnormal or missing peristalsis, this clearance of interstitial fluid is impaired. Furthermore, mechanical ventilation with high intra-thoracic pressure (ITP) can affect lymph flow, by impeding lymphatic return, while the concomitant increase in splanchnic venous pressure may result in a net increase in lymph production favouring oedema formation [57,58].…”
Section: Abdominal Lymph Flow In Critically Ill Patients With Iahmentioning
confidence: 99%